Kajian Media Massa: Representasi Girl Power Wanita Modern dalam Media Online (Studi Framing Girl Power dalam Rubrik Karir dan Keuangan Femina Online) - Aprinta, Gita (Jurnal The Messenger, 2011)
The working women isn t a new phenomenon in the modern society. Through their carrier, they try to find meaning, identity and achievement that bring confidence to their life. However, there is still a problem regarding the bias gender related to the quality and capabilities of women in the work field. Femina as one of women magazine realize that women also need information that can help them to attributes and give the self identity in the role of society. This research aim at how Femina talks about girl power in several articles by Gamson and Modigliane framwork in two core structures and condensing symbol frames.